2015
DOI: 10.9734/ajea/2015/12099
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Informal Credit on Agriculture: An Assessment of Small Scale Maize Farmers Utilization of credit in Jema`a Local Government Area of Kaduna State, Nigeria

Abstract: The work involved the all authors. Authors HO and PI prepared the questionnaire and collected the data for the research. They also wrote the first draft of the manuscript and managed the analyses of the data. Author OY, HY and HS managed the research design, literature searches, and report writing. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…It may also be that during repayment, friends and family members may not request any form of interest. This agrees with findings of Yusuf et al (2015), who found that a major source of informal credit was from family and friends. The major formal source of credit accessed by marketers was the microfinance bank followed by cooperative bank; the least common source of formal credit among marketers was commercial banks.…”
Section: Resultssupporting
confidence: 92%
“…It may also be that during repayment, friends and family members may not request any form of interest. This agrees with findings of Yusuf et al (2015), who found that a major source of informal credit was from family and friends. The major formal source of credit accessed by marketers was the microfinance bank followed by cooperative bank; the least common source of formal credit among marketers was commercial banks.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, there is disagreement in the extant literature about the role of informal credit. Some studies reveal that informal credit is terrible for farmers' livelihood [27,28], while others verify its crucial function in economic development [29,30]. These contentions further intensify the generalization of the existing literature on informal credit to Afghanistan.…”
Section: Introductionmentioning
confidence: 99%
“…The fund's liability is limited to 75% of the amount in default net of any amount realized by the lending bank from the sale of the security pledged by the borrower. Since the inception of the scheme in 1978, the aggregate number of loans to agriculture hasalways been on the rise from a negligible number of 341 loans amounting to 11.28 million NGN (18,613,861 USD) in 1978 to 3,571 loans valued at 218.60million NGN (1,679,600.46 USD) as at May, 2006(Yusuf et al, 2015.…”
Section: Introductionmentioning
confidence: 99%